Unusual π–π interactions directed by the [(C6H6)Ru2W8O30(OH)2]6− hybrid anion. Issue 23 (24th May 2021) - Mukhacheva, Anna A.; Komarov, Vladislav Yu.; Kokovkin, Vasily V.; Novikov, Alexander S.; Abramov, Pavel A.; Sokolov, Maxim N.
Abstract : The [(C6 H6 )Ru2 W8 O30 (OH)2 ] 6− hybrid anion as a new type of π–π stacking induced building block and methanol oxidation precatalyst. Abstract : The [(C6 H6 )Ru2 W8 O30 (OH)2 ] 6− hybrid (organometallic–POM) anion was used as a pH-tunable building block to create special conditions for realizing π–π interactions in the crystal structure. Changing the pH of an aqueous solution of Na6 [(C6 H6 )Ru2 W8 O28 (OH)2 ]·16H2 O (1 ) results in isolation of a series of new compounds with different Na + /H + ratios in the cationic composition: Na5.5 H0.5 [(C6 H6 )Ru2 W8 O28 (OH)2 ]·15H2 O (2 ), Na5 H[(C6 H6 )Ru2 W8 O28 (OH)2 ]·22H2 O (3 ), Na4 H2 [(C6 H6 )Ru2 W8 O28 (OH)2 ]·24H2 O (4 ), Na3 H3 [(C6 H6 )Ru2 W8 O28 (OH)2 ]·23H2 O (5 ), and NaH5 [(C6 H6 )Ru2 W8 O28 (OH)2 ]·9H2 O (6 ). All complexes were characterized by single crystal X-ray diffraction (SCXRD) analysis and ICP-AES. The presence of π–π stacking was detected for moderate-to-highly protonated 3–6 . The energy of such interactions was calculated to increase in the following order: 6 (5.0 kJ mol −1 ) < 5 (7.6 kJ mol −1 ) < 3 (10.0 kJ mol −1 ). 1 was studied for its electrochemical behavior in 0.5 M Li2 SO4 and as a paste electrode component in methanol. Catalytic activity in methanol oxidation was detected.